2019
DOI: 10.1002/piq.21288
|View full text |Cite
|
Sign up to set email alerts
|

Building a Cognitive Readiness for Violent Police–Citizen Encounters: A Task Analysis

Abstract: Results from a number of studies indicate that a multitude of factors influence human dynamics and outcomes associated with the application of force by police. Little research has been done to understand the cognitive processing associated with rapid assessment and response to such encounters. In order to enhance the body of knowledge, this exploratory study employed cognitive task analysis (CTA) methods to examine the concept of cognitive readiness in the context of violent police–citizen encounters. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“… Hamilton et al (2019) showed that cognitive training can improve shooting performance in law enforcement situations. These findings are consistent with Preddy et al (2019) , who suggested that cognitive readiness in the context of critical encounters in a law enforcement context should be supported by skill training in the areas of domain and prerequisite knowledge, pattern recognition, and situational awareness.…”
Section: Introductionsupporting
confidence: 90%
“… Hamilton et al (2019) showed that cognitive training can improve shooting performance in law enforcement situations. These findings are consistent with Preddy et al (2019) , who suggested that cognitive readiness in the context of critical encounters in a law enforcement context should be supported by skill training in the areas of domain and prerequisite knowledge, pattern recognition, and situational awareness.…”
Section: Introductionsupporting
confidence: 90%
“…Although the literature is critical of the structure and delivery of police training, empirical investigation of how training is actually delivered is limited to the perspective of the trainees (learners) and coaches (trainers) (i.e. Preddy et al 2019a;Rajakaruna et al 2017 and to a specific component of police training (i.e., officer safety training, Cushion 2020). Furthermore, when generalising the findings of police training it is important to be cognisant of differences in national socio-economic context.…”
Section: Introductionmentioning
confidence: 99%
“…never before seen attacking behaviour of citizen), SOPs have to be abandoned and behaviour has to be adapted according to the situation (Boulton and Cole, 2016; Schakel et al, 2016). As such, the skill to adapt to changing circumstances has been described as a core competency in police field work, especially in the context of conflict (Boulton and Cole, 2016; Preddy et al, 2019a; Staller and Zaiser, 2015). Likewise, accounts of the recruits in the current study included the need for flexibility and adaptivity as operational competencies in police work.…”
Section: Discussionmentioning
confidence: 99%